США В ПОИСКАХ ОТВЕТА НА ИРАНСКИЙ ВЫЗОВ: КУРДСКИЙ КЕЙС, НОЯБРЬ – ДЕКАБРЬ 1979 ГОДА (Вестник Пермского университета. История = Perm University Herald. History ISSN 2219-3111, 2023)
As a result of the capture of the American embassy by supporters of the supreme leader of the Islamic Republic of Iran, Ayatollah R. Khomeini, the U.S. lost the chances for a quick restoration of its positions in the Middle East. The events unfolding in Tehran demanded a serious and balanced response from the administration of John Carter. Under these conditions, the American government and its analytical structures began to look for tools to influence and put pressure on the Islamic regime. One of the potential levers of American policy could be the Kurdish issue, which was again openly put on the agenda after the Islamic revolution of 1978–1979. The potential of the Iranian Kurds in terms of countering the Khomeini regime, their controllability and the conformity of their struggle with U.S. interests have become the subject of analytical work of the state services. The article examines the place and role of the Kurdish question in the search for U.S. responses to the challenges of the Iranian crisis caused by the capture of the U.S. embassy in November 1979. Based on a wide range of documents from the U.S. National Archives, the John Carter Presidential Library, the State Department, the Central Intelligence Agency and the Council of National U.S. security, the author traces the course of developing a policy towards Iran and a position regarding the national movement of Iranian Kurds. The context of regional policy and the influence of the Afghan issue on the Iranian course of Washington are also traced. As a result of the development of decisions, the line of Secretary of State S. Vance prevailed, demanding to refrain from active aggressive actions against Iran, to ignore the Kurdish movement. The entry of Soviet troops into Afghanistan also had an impact, turning the entire political situation in the Middle East upside down.